Comparison of Nutritive Values of Tropical Pasture Species Grown in Different Environments, and Implications for Livestock Methane Production: A Meta-Analysis - Jayasinghe P; Ramilan T; Donaghy DJ; Pembleton KG; Barber DG (MDPI (Basel, Switzerland), 2022)
The demand for dairy products is ever increasing across the world. The livestock sector is a significant source of greenhouse gas (GHG) emissions globally. The availability of high-quality pasture is a key requirement to increase the productivity of dairy cows as well as manage enteric methane emissions. Warm-season perennial grasses are the dominant forages in tropical and subtropical regions, and thus exploring their nutritive characteristics is imperative in the effort to improve dairy productivity. Therefore, we have collated a database containing a total of 4750 records, with 1277 measurements of nutritive values representing 56 tropical pasture species and hybrid cultivars grown in 26 different locations in 16 countries; this was done in order to compare the nutritive values and GHG production across different forage species, climatic zones, and defoliation management regimes. Average edaphoclimatic (with minimum and maximum values) conditions for tropical pasture species growing environments were characterized as 22.5 °C temperature (range 17.5-29.30 °C), 1253.9 mm rainfall (range 104.5-3390.0 mm), 582.6 m elevation (range 15-2393 m), and a soil pH of 5.6 (range 4.6-7.0). The data revealed spatial variability in nutritive metrics across bioclimatic zones and between and within species. The ranges of these nutrients were as follows: neutral detergent fibre (NDF) 50.9-79.8%, acid detergent fibre (ADF) 24.7-57.4%, crude protein (CP) 2.1-21.1%, dry matter (DM) digestibility 30.2-70.1%, metabolisable energy (ME)3.4-9.7 MJ kg-1 DM, with methane (CH4) production at 132.9-133.3 g animal-1 day-1. The arid/dry zone recorded the highest DM yield, with decreased CP and high fibre components and minerals. Furthermore, the data revealed that climate, defoliation frequency and intensity, in addition to their interactions, have a significant effect on tropical pasture nutritive values and CH4 production. Overall, hybrid and newer tropical cultivars performed well across different climates, with small variations in herbage quality. The current study revealed important factors that affect pasture nutritive values and CH4 emissions, with the potential for improving tropical forage through the selection and management of pasture species.
Keywords: dairying; grasses; meta-analysis; methane; quality; tropical pasture